A kinase associated with chromatin that can be activated by ligand-p185c-Neu or epidermal growth factor-receptor interactions. - Samanta, A (1995)
Some growth factors transduce positive growth signals, while others can act as growth inhibitors. Nuclear signaling events of previously quiescent cells stimulated with various growth factors have been studied by isolating the complexed chromatin-associated proteins and chromatin-associated proteins. Signals from the plasma membrane are integrated within the cells and quickly transduced to the nucleus. It is clear that several growth factors, such as epidermal growth factor, transforming growth factor alpha (but not transforming growth factor beta), and platelet-derived growth factor, utilize similar intracellular signaling biochemistries to modulate nucleosomal characteristics. The very rapid and consistent phosphorylation of nuclear p33, p54, and low molecular mass proteins in the range of 15-18 kDa after growth factor stimulation implies that there is a coordination and integration of the cellular signaling processes. Additionally, phosphorylation of p33 and some low molecular mass histones has been found to occur within 5 min of growth factor treatment and to reach a maximum by 30 min. In this study, we report that Neu receptor activating factor also utilizes the same signaling mechanism and causes p33 to become phosphorylated. In addition, both the tumor promoter okadaic acid (which inhibits protein phosphatases 1 and 2A) and phorbol ester (phorbol 12-tetradecanoate 13-acetate) stimulate phosphorylation of p33, p54, and low molecular mass histones. However, transforming growth factor beta, which is a growth inhibitor for fibroblasts, fails to increase p33 phosphorylation. In general, p33 phosphorylation patterns correspond to positive and negative mitogenic signal transduction. p33 isolated from the complexed chromatin-associated protein fraction appears to be a kinase, or tightly associated with a kinase, and shares antigenicity with the cell division cycle-dependent Cdk2 kinase as determined by antibody-dependent analysis. The rapid phosphorylation of nucleosomal proteins may influence sets of early genes needed for the induction and progression of the cell cycle.